An introduction to programming using Python - Schneider, David I. (Always learning., 2016)
Introduction to Programming Using Python is designed for students eager to learn about the world of programming. Applicable to a range of skill levels, this First Edition textbook provides students with the tools to harness the powerful syntax of Python and understand how to develop computer programs. The compactly written text leverages highly focused chapters, diving deep into the most significant topics to give students an in-depth (rather than superficial) understanding of the language. Using real-world examples and data, the author illustrates practical usage of Python in a way to which students can relate. The text itself is readable, organized, and informative, discussing main points of each topic first and then addressing the peripheral details. Students learn good programming habits the first time-bringing them in line with the best modern programming practices.